Central China,1852
includes letters from:- Walter Medhurst, Shanghai - 10,000 copies of revised New Testament in Chinese printed and circulated Joseph Edkins, Shanghai - half-yearly report joint letters from Walter Medhurst and John Stronach, Shanghai joint letter from Walter Medhurst, William Milne and John Stronach, Shanghai Dr William Lockhart, Shanghai - Alexander Wylie, Shanghai William Muirhead, Shanghai William Milne, Shanghai - half-yearly report Mary Ann Aldersey, Ningpo [Ningbo]